2018
DOI: 10.2967/jnmt.117.203547
|View full text |Cite
|
Sign up to set email alerts
|

A Microdose PET Study of the Safety, Immunogenicity, Biodistribution, and Radiation Dosimetry of18F-FB-A20FMDV2 for Imaging the Integrin αvβ6

Abstract: The αβ integrin is involved in the pathogenesis of cancer and fibrosis. A radiolabeled 20-amino-acid αβ-binding peptide, derived from the foot and mouth virus (NAVPNLRGDLQVLAQKVART [A20FMDV2]), has been developed to image αβ levels preclinically. This study was designed to translate these findings into a clinical PET imaging protocol to measure the expression of αβ in humans. Preclinical toxicology was undertaken, and a direct immunoassay was developed for 4-fluorobenzamide (FB)-A20FMDV2. Four healthy human su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…[ 18 F]FB-A20FMDV2 is a potent, selective ligand for integrin αvβ6, as shown by in vitro cell-free and cellular binding assays [18,30,31] and by in vivo animal models of cancer [25,32] and pulmonary fibrosis [33,21]. In addition, it has been tested in a first dose in human study of the safety, tolerability, biodistribution, radio-dosimetry and immunogenicity of [ 18 F]FB-A20FMDV2 [20]. Visual inspection of these PET images from healthy humans suggested that uptake of radioactivity was observed in the thyroid, salivary glands, liver, stomach wall, spleen, ureters and bladder [20].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[ 18 F]FB-A20FMDV2 is a potent, selective ligand for integrin αvβ6, as shown by in vitro cell-free and cellular binding assays [18,30,31] and by in vivo animal models of cancer [25,32] and pulmonary fibrosis [33,21]. In addition, it has been tested in a first dose in human study of the safety, tolerability, biodistribution, radio-dosimetry and immunogenicity of [ 18 F]FB-A20FMDV2 [20]. Visual inspection of these PET images from healthy humans suggested that uptake of radioactivity was observed in the thyroid, salivary glands, liver, stomach wall, spleen, ureters and bladder [20].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been tested in a first dose in human study of the safety, tolerability, biodistribution, radio-dosimetry and immunogenicity of [ 18 F]FB-A20FMDV2 [20]. Visual inspection of these PET images from healthy humans suggested that uptake of radioactivity was observed in the thyroid, salivary glands, liver, stomach wall, spleen, ureters and bladder [20]. Immunohistochemistry and SPECT imaging of healthy rodent tissues revealed that αvβ6 is expressed constitutively in the epithelium of the gall bladder, stomach wall, duodenum, ileum, colon, and at lower levels in the lungs and skin [34,35]; largely supporting the observed expression in healthy humans [20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations